New Product Fumbles - Organizing for the Ramp-up Process - Irene Christensen (Copenhagen Business School (CBS), 2018)
This study examines rapid prototyping, also referred to as new production launch, or ramp-up time. A strong emphasis on speed is vital for the success of a product development and market launch. Managers concern themselves with organizing ramp-up activities into arrayed sequences to achieve production launch goals. These sequences are not only regarding prearranged linear milestones, but extensively reviewed and often reorganized complex activities, with the managerial goal of a wellconfigured productive process. The need to manage the final phase in product development is evident, because many of the failures leading to product launch delays have multiple root causes, ranging from poorly understood and overly engineered novel technologies to a “throw it over the wall” approach between development functions and inexperienced machine operators, in addition to high complexity levels in quality testing. The study examines these complexities through social theoretical lenses. In doing so, an in-depth qualitative approach has been employed with the aim of addressing the fundamental barriers in the advancement of this managerial field, and the practical complexities in managing this specific part of the development of products. This has been achieved by longitudinally studying a total of eight major development cases at a large Scandinavian manufacturing company over a period of three years. These development projects faced different challenges during the interface between R&D and ramp-up production, resulting in delays in product launch. Drawing on the results of this real-time study, the thesis contributes with (i) a conceptual model for lean management application to the ramp-up process, (ii) the advancement of clinical methodological approach for in-depth studying of the ramp-up management phenomena, (iii) cause and effects of ramp-up activities delays, and (iv) managerial strategies for managing organization-environment interdependencies.
hdl:10398/9617
Keywords: 650